MODEL JIGSAW DIAPLIKASIKAN PADA MATA KULIAH IPA TERPADU - Yuliana Yenita Mete; Maimunah H. Daud (Jurnal Bionatural, 2025)
The purpose of applying the jigsaw cooperative learning model in order to improve student learning outcomes in SMP SATAP 7 Nangapada. This type of research is classroom action research (CAR). Research subjects in class VIII, with a total of 21 students consisting of 10 women and 11 men. Data collection techniques using the method of observation, interviews, documentation, and tests. The data analysis technique uses descriptive qualitative. The results of the study prove that using a jigsaw learning model can improve student learning outcomes in SMP SATAP 7 Nangapanda. Can be shown by the percentage of completeness of pre-learning outcomes 42, 85%, 71.42% first cycle, second cycle 100%.